Assessing Farmers’ Flood Vulnerability and Institutional Role in Mitigating Its Impacts in District Jamshoro, Sindh (Journal of Asian Development Studies, 2023)
Floods in Pakistan are a constant and destructive phenomenon that causes significant economic and social losses. Therefore, this study aimed to assess farmers' flood vulnerability and institutional role in mitigating its impacts in district Jamshoro, Sindh. To collect samples, 150 individuals living in the Jamshoro district, the area most badly damaged by floods, were chosen randomly and non-probabilistically to gather primary data. Questionnaires were administered, and interviews were conducted with respondents. In addition, relevant technical reports, policy documents, and research papers related to flood management studies were reviewed as secondary data. Statistical analysis of the collected data was undertaken using t-tests. The results revealed that economic impacts were severe, with 82% of farmers reporting crop damage or destruction and 75% reporting reduced yield. Moreover, most farmers (57%) reported a more than 50% decrease in income. The floods also had significant social impacts, with 98% of respondents reporting damage or destruction of homes and 95% reporting displacement of families. The analysis also showed that farmers in the study area were very vulnerable to flooding, where livestock damage was reported by 37.3% of the respondents, crop loss by 28%, and housing devastation by 14.6%. The findings revealed that institutions were moderately successful in reducing the effects of floods, with an average efficiency rating of 3.5. This study also highlighted that access to information and involvement in decision-making were the most significant factors affecting institutions' effectiveness, with 70% and 60% of the respondents reporting these factors.